Phase angle as a novel indicator of sarcopenic obesity in patients undergoing hemodialysis - Cheng, Linghong; Chang, Liyang; Yang, Ruchun; Tian, Rongrong; Xiong, Manting; Zhang, Hongmei (Frontiers in Nutrition, 2025)
BackgroundThe relationship between phase angle (PhA) and sarcopenic obesity (SO) in patients undergoing hemodialysis (HD) has not been well established. Therefore, this study aimed to evaluate the relationship between PhA and SO in patients undergoing HD and to determine the cutoff value of PhA that can predict SO.MethodsWe conducted a cross-sectional study of 436 patients undergoing HD. The PhA was measured by bioelectrical impedance analysis. SO was diagnosed according to the revised definition of the Asian Working Group for Sarcopenia combined with obesity based on body fat percentage. The association between PhA and SO was assessed using multinomial logistic regression. The PhA cutoff values for SO were determined using receiver operating characteristic (ROC) curve analysis.ResultsAmong the participants, 119 (27.3%) had SO. After adjusting for various confounders, PhA was significantly associated with a lower SO risk [odds ratio (OR) = 0.098, 95% confidence interval (CI): 0.048–0.200]. Furthermore, PhA showed a stronger association with SO than with sarcopenia or obesity alone. ROC analysis indicated excellent predictive ability for SO in both sexes (area under the curve (AUC): 0.841 for males, 0.836 for females; cutoff values: 4.49° for males, 4.18° for females).ConclusionPhA exhibited good accuracy in detecting SO in patients undergoing HD, suggesting its utility as a reliable screening tool for the early identification of at-risk individuals.